Dynamic Functional Connectivity Signifies the Joint Impact of Dance Intervention and Cognitive Reserve - Mitterová, Kristína; Lamoš, Martin; Mareček, Radek; Pupíková, Monika; Šimko, Patrik; Grmela, Roman; Skotáková, Alena; Vaculíková, Pavlína; Rektorová, Irena (Frontiers in Aging Neuroscience, 2021)
Research on dance intervention (DI) in the elderly has shown promising benefits in physical and cognitive outcomes. The effect of DI on resting-state functional connectivity (rs-FC) varies, possibly due to individual variability. We assessed the moderation effects of residual cognitive reserve (CR) on DI-induced changes in dynamic rs-FC and their association with cognitive outcomes. Dynamic rs-FC (rs-dFC) and cognitive functions were evaluated in non-demented elderly subjects before and after a six-month DI (n=36) and in a control group (life as usual, LAU; n=32). Using linear mixed models and moderation, we examined the interaction effect of DI and CR on changes in dwell time and coverage of rs-dFC. CR was calculated as a residual difference between the observed memory performance and the performance predicted by brain state. Partial correlations accounting for CR evaluated the unique association between changes in rs-dFC and cognition in the DI group. In subjects with lower residual CR, we observed a DI-induced increase of dwell time (t(58) = -2.14, p = .036) and coverage (t(58) = -2.22, p = .030) of the rs-dFC state implicated in bottom-up information processing. Increased dwell time correlated with DI-induced improvement on Symbol Search (r = .42, p = .02). In subjects with higher residual CR, we observed DI-induced increased coverage (t(58) = 2.11, p = .039) of the rs-dFC state implicated in top-down information processing. The study showed that DI has a differential, behaviorally relevant effect on dynamic rs-dFC and that these benefits depend on the current CR level.